Oral isotretinoin for acne vulgaris side effects on the ocular surface: Hyaluronic acid and galacto-xyloglucan as treatment for dry eye disease signs and symptoms - Sánchez-González, María Carmen; De-Hita-Cantalejo, Concepción; Martínez-Lara, Concepción; Sánchez-González, José-María (Frontiers in Medicine, 2022)
The purpose was to assess the efficacy of 0.4% hyaluronic acid and 0.2% galacto-xyloglucan on the subjective symptoms of dry eye disease and invasive and noninvasive tear film signs in oral isotretinoin for acne vulgaris treatment. A prospective, longitudinal, single-blind, clinical study was performed in oral isotretinoin for the acne vulgaris consumer population. Subjective dry eye disease questionnaires and invasive and noninvasive tear film assessments were reported prior to and after six weeks of hyaluronic acid with galacto-xyloglucan (HA-GX) treatment versus hyaluronic acid alone (HA). Participants in the HA-GX group reported a higher decrease in the ocular surface disease index (17.01 ± 11.36 score points) compared to the variation in participants in the HA group (11.61 ± 11.18 score points). Standard patient evaluation of eye dryness also decreased more in participants in the HA-GX group (4.06 ± 5.50 score points) than in participants who received HA alone (0.70 ± 3.16). Regarding noninvasive break-up time (NIBUT), participants in the HA-GX group first NIBUT achieved an increase of 1.75 ± 1.16 seconds while participants in the HA-alone group demonstrated an increase of only 0.54 ± 1.01 seconds. The HA-GX group mean NIBUT increased by of 3.72 ± 5.69 seconds; however, the value for the HA-alone group was 2.19 ± 5.26 seconds. Hyaluronic acid in combination with galacto-xyloglucan significantly decreased limbal and bulbar conjunctival redness classification and SPEED test outcomes. The inclusion of galacto-xyloglucan also increased BUT and mean NIBUT values compared to those obtained with hyaluronic acid alone.